The Ties that Bind: Monetary Policy and Government Debt Management - Jagjit S. Chadha; Philip Turner; Fabrizio Zampolli (University of Kent, School of Economics, 2013)
The financial crisis and subsequent economic recession led to a rapid increase in the issuance of public debt. But large-scale purchases of bonds by the Federal Reserve, and other major central banks, have significantly reduced the scale and maturity of public debt that would otherwise have been held by the private sector. We present new evidence that tilting the maturity structure of private sector holdings significantly influences term premia, even outside crisis times. Our framework helps explain both the bond yield conundrum and the effectiveness of quantitative easing. We suggest that these findings raise two important policy questions. One is: should a central bank, contrary to recent orthodoxy, use its balance sheet as an additional complementary instrument of monetary policy to influence, as part of the monetary transmission mechanism, the long-term interest rate? The second is: how should central banks and governments ensure that debt management properly takes account of the implications for both monetary and financial stability?
Keywords: E43; E52; E63; 330; Quantitative easing; sovereign debt management; long-term interest rate; portfolio balance effect; exit strategy